Architectured multi-metal CoCrFeMnNi-Inconel 718 lamellar composite by high-pressure torsion. (1st April 2021) - Karthik, G.M.; Asghari-Rad, Peyman; Sathiyamoorthi, Praveen; Zargaran, Alireza; Kim, Eun Seong; Kim, Taek Soo; Kim, Hyoung Seop
Abstract: Multi-metal composites have gained much interest in recent years to explore the unfilled space of the strength-elongation window. However, producing these composites is challenging and is limited to a few material combinations because most processing techniques involve melting/solidification and high-temperatures. This work demonstrates a new powder metallurgy-based approach to produce these composites using high-pressure torsion. Lamellar nano-crystalline composite with high entropy alloy (CoCrFeMnFe) matrix and uniformly distributed nickel-base superalloy (Inconel 718) reinforcement are realized after high-pressure torsion. The current approach has resulted in an excellent metallurgical bonded interface with an ultra-fine grain size in both the matrix and reinforcement. The samples showed an exceptional synergy of high yield strength 900 MPa and elongation 40%, overcoming the perennial challenge in multi-metal composites. The current approach is versatile and can open up a horizon of multi-material combinations with a synergy of strength and ductility. Graphical abstract: Image, graphical abstract